The position of idols is the belief of the pre-Islamic pagans (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research has focused on the status of idols in the belief of the pagans of the pre-Islamic Arabs. It starts off by mentioning the construction of our master Ibrahim (PBUH) the ancient house in Mecca as the first Arabic place in and around which idols were erected. Then the relationship of the body of Adam (PBUH) with the first idol known to humanity is highlighted, moving, after that, to talking about the first idols known to mankind in India, which were swept away by the flood of Noah from Mount Nouz in India to the city of Jeddah in the Arabian Peninsula. Those idols were then brought by the servant of Kaaba, at the time, Amru Bin Luhai, to Mecca. There, he called on the Abrahamic Arabs pilgrims of the ancient House to venerate them, and to draw closer to God by circumambulating and turning around them, following in the steps of the Cain people who made the first idol symbolizing the body of their father, Adam. After that, we have talked about the struggle of  Ismail bin Ibrahim people with each other over the residence in Mecca, a struggle that resulted in some of them forced to leave. Those who left took stones from Mecca as a souvenir, and those stones were erected anywhere they lived in the land of the Arabian Peninsula, and became Idols for them in their homes, circumambulating them, which spared them the trouble of traveling to Mecca to circumambulate its idols. Next, the focus of this research has shifted to the norms and rituals of worship among the Arabs, since Abraham called people to the pilgrimage to the ancient house, until the advent of Islam, shedding light on some of their habits and social customs related to religion, and on the rituals of their pilgrimage at the time of our master Ibrahim, before they became acquainted with idols. Then these customs and social norms, together with religious rituals, has been compared with the corresponding customs and customs of the pre-Islamic Arabs, and the rituals of pilgrimage among the pagan Arabs, but rather among the Muslims after them. We have found no differences in the way of resorting to worshipping God among the doctrine of Arabs related to Ibrahim, before and after their knowledge of idols, and later that doctrine of the Muslims who demolished the idols with their own hands; The one and only God is the deity that the Arabs turned to in worship, since they made a pilgrimage to the ancient house at the time of our master Ibrahim, passing through the pilgrimage to it after its sides were surrounded by idols, up to the rituals of the Muslims’ pilgrimage to the ancient house, after they stripped it of its idols and returned it to The form in which our master Ibrahim left; the innocence of the pagans from worshiping idols, but rather from worshiping other than God, idols or non-idols, has been, for us, clear and evident, in their striking those idols, and their drawing closer to God by slaughtering sacrifices there, and in their insistence, according to the Holy Qur’an, that they do not worship idols. They only draw closer to God through them, and their innocence from idolatry has been clear to us through their rebuke and reproach of idols, whenever they were disappointed in them, and saw what they did not like. This was also reflected in their enemies’ confirmation of their God’s monotheism, reflected in the words of some of their opponents: “The pagans used to unite God with the Talbiyah, … and make their idols’ possession in His hand.”